Mapping giant honey bee nests in Palawan, Philippines through a transdisciplinary approach. Issue 7 (3rd October 2017) - Matias, Denise Margaret S.; Stellmacher, Till; Borgemeister, Christian; Cayron, Jun G.; von Wehrden, Henrik
ABSTRACT: This article reports on a study that uses participatory mapping with indigenous Tagbanua honey hunters and gatherers to understand the spatial distribution of giant honey bees in a community forest in Palawan, Philippines. Through the use of global positioning system devices, digital cameras, and a solar home system as an electricity source, local collaborators mapped 31 bee nests from April to June 2015. This study provides a replicable long-term participatory methodology and promotes participatory learning and mutual knowledge creation. By combining applied sustainability research with local stakeholder participation, the article suggests that novel knowledge and solutions can aid sustainable rural development.